Study of Income Over Feed and Chick Cost Efficiency of Broiler fed on Sea Grass - M. B. Rombe (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2012)
The purpose of this study was to evaluate the benefit of giving diets containing sea grass on feed efficiency of broiler production for maximum economic returns. Ninety one-day-old SUR-707 unisexes of broilers chicken were randomly assigned into three groups of dietary treatments according to completely randomised design. The replications for each treatment were six giving total experimental unit of 18. Five broiler chicken were allocated for each replication/experimental unit. The dietary treatments were 0% sea grass (N0), 4.5% sea grass Euchema cottonii (N1), and 4.5% sea grass gracillaria verucosa (N2). Experimental diets were formulated to be iso-protein (19.5%) an iso-calorie (4000 kcal/kg). Variables measured were feed consumption, body weight, feed conversion, and income over feed and chick cost (IOFCC). Results of the study indicated that feed consumption, body weight, feed conversion, and IOFCC were affected by the treament. The lowest IOFCC was obtained for broilers fed on diet containing no sea grass (No) compared with other treatments (N1 and N2). Between diets containing sea grass, the IOFCC for broilers given diet with Gracillaria verucosa (N2) was higher compared to that given diet with Euchema cottonii (N1). In conclusion, addition of sea grass into broiler ration could improve the IOFCC.